Peningkatan Kompetensi Guru PAI dalam Menghadapi Revolusi Digital: Enhancing Islamic Education (PAI) Teachers' Competence in Facing the Digital Revolution - Zubaidah, ST. (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2023)
The application and utilization of digital technology in the social sphere have given rise to new ways for the community to absorb religious information. Currently, the ability for critical evaluation (tabayun) is essential for everyone to possess when absorbing religious information, including students, in order to avoid misunderstandings that are not in line with the teachings of Islam in Indonesia. Enhancing the professional competence of Islamic religious education (PAI) teachers in facing this digital revolution is highly necessary to build the filtering capabilities of students when consuming digitally-based religious content. The objectives of this research are: (1) to assess the professional competence of PAI teachers in facing the digital revolution, (2) to explore the methods that should be used to enhance their professional competence, and (3) to identify the obstacles to improving professional competence in facing the digital revolution and propose solutions. The research approach employed in this study is a qualitative case study method, while data collection techniques involve interviews based on researcher-prepared guidelines and observations. The findings from the research indicate that there are three fundamental aspects that need improvement in relation to enhancing professional competence in facing the digital revolution: (1) PAI teachers should enhance their knowledge about digital technology products, (2) PAI teachers should deepen their understanding of the digitalization of religious teachings, and (3) PAI teachers should improve their comprehension of the character of Islamic teachings in Indonesia. Keyword: Professional, Competence, Teacher Islamic Religious Education (PAI), Digital Revolution ABSTRAK Penerapan dan pemanfaatan teknologi digital dalam ruang lingkup sosial melahirkan cara baru bagi masyarakat dalam menyerap informasi keagaamaan, pada saat ini kemampuan tabayun mutlak harus dapat dimiliki oleh semua orang dalam menyerap informasi keagaamaan termasuk siswa agar terhindar dari pemahaman-pemahaman yang tidak sesuai dengan karakter ajaran Islam di Indonesia. Peningkatan kompetensi profesional guru PAI dalam menghadapi revolusi digital ini sangat diperlukan untuk membangun kemampuan filterisasi peserta didik dalam mengkonsumsi konten-konten keagamaan yang berbasis digital. Tujuan dari penelitian ini adalah (1) mengetahui kompetensi profesional guru PAI menghadapi revolusi digital (2) meneliti metode yang harus digunakan untuk meningkatkan kompetensi profesional (3) Menggali dan menemukan kendala-kendala peningkatan kompetensi profesional dalam menghadapi revolusi digital beserta solusinya. Metode pendekatan yang dilakukan dalam penelitian ini adalah metode case study pendekatan kualitatif, sedangkan teknik pengumpulan data yang dilakukan oleh peneliti yaitu dengan menggunakan teknik wawancara berdasarkan pedoman wawancara yang peneliti telah buat dan observasi. Hasil temuan yang peneliti dapatkan dari penelitian menunjukan bahwa ada 3 hal mendasar yang yang harus ditingkatkan berkaitan dengan peningkatan kompetensi profesional dalam menghadapi revolusi digital, (1) guru PAI harus meningkatkan pengetahuannya tentang produk-produk dari teknologi digital (2) guru PAI harus meningkatkan pemahamannya tentang fenomena digitalisasi ajaran, dan (3) guru PAI harus meningkatkan pemahamannya terkait karakter pemahaman ajaran Islam di Indonesia. Keyword: Kompetensi, Professional, Guru PAI, Revolusi digital